COMPRESENZE: DONNE E RELIGIONI A SUD - Irene Strazzeri (Studia Paradyskie)
Religious identity overload usually interacts with cultural identity and gender overload. Religious identity ceases to be the difference trough which single persons can continue to exist in equal relationship. Gender identity reveals, on the contrary, all the problems and conflicts rooted in the respective cultural, religious, social and political spheres. Study and research, training and the assumption of a critical attitude would turn this system upside down, whatever the geographical and social place in which it is located.